Effectiveness Of Using The Method Of Storytelling In Improving Students' Learning Interest In The Prophet's Story Material At MI NWDI In The Environment - Firdaus, Giwa Iqbal; Rizal, Syamsul (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effectiveness of applying the storytelling method in increasing students' interest in learning about the stories of the Prophet at MI Nahdlatul Wathan Diniah Islamiah (NWDI) Lingkung. The main problem faced is the low motivation and involvement of students in learning Islamic Cultural History (SKI), which is still dominated by conventional lecture methods. This study used a quantitative approach with a One-Group Pretest–Posttest design and involved 24 fourth-grade students as respondents. The research instruments included learning outcome tests, activity observations, and Likert scale questionnaires to measure four indicators of learning interest, namely attention, enjoyment, involvement, and perceived benefits. The results showed a significant increase in all indicators after the storytelling method was implemented. The average questionnaire score increased from 3.04 to 4.47, with the highest increase in the aspects of enjoyment and perceived benefits. Student learning activities also increased from 46% to 86%, and the average learning outcome score rose from 62.3 to 83.1. This increase proves that the storytelling method is effective in fostering students' interest, motivation, and understanding of the moral and spiritual values in the stories of the Prophets. Thus, storytelling is a viable alternative strategy for SKI learning that is more active, inspiring, and meaningful.